INTRODUKSI TEKNOLOGI DALAM MENUNJANG USAHA TERNAK ITIK DI DESA PASLATEN KECAMATAN KAKAS KABUPATEN MINAHASA - Rundengan, Meiske L; Elly, F H; Lumenta, I D.R; Kalangi, L S; Lumi, T F.D; Poli, Z (ZOOTEC, 2020)
INTRODUCTION OF TECHNOLOGY IN SUPPORT FARMING OF DUCK IN PASLATEN VILLAGE DISTRICT OF KAKAS REGENCY OF MINAHASA.The purpose of raising ducks by members of the Kinakas Jaya group was to produce eggs and meat. The eggs produced were around 60-70 percent of the total number of duck members owned by group members. The low production andÂ productivity of ducks causes low income received by group members and not continuous whereas the demand for duck products has increased from year to year. Duck farming in North Sulawesi has a very large development prospect in terms of the population that tends to increase every year. The problem with raising ducks by group members was still traditional and the availability of DOD was not continuous. Based on these problems, empowerment of group members was carried out, namely extension and introduction of hatching machines. The research was conducted with the aim to find out the extent of empowerment activities in supporting duck business in Paslaten Village, Kakas District. The research method used was a survey method. The sample location was Paslaten Village, which was determined by purposive sampling (a village with a group of duck farmers). Respondents were members of the Kinakas Jaya group who were empowered through the introduction of technology. The age of the respondents ranged from 42-50 years with junior high school level (37.5%) and high school 62.5%. Extension was done and responded well by group members. Furthermore, the process of hatching eggs was carried out by group members. Based on the results of the study it can be concluded that the technology was successfully adopted by group members, but the success rate of hatching eggs was still low. Suggestions submitted need to increase the frequency of counseling and application of technologyÂ